An engineered lithocholate-based facial amphiphile stabilizes membrane proteins: assessing the impact of detergent customizability on protein stability - Das,M; Du,Y; Mortensen,JS; Bae,HE; Byrne,B; Loland,CJ; Kobilka,BK; Chae,PS (Chemistry: A European Journal, 2018)
Amphiphiles are critical tools for the structural and functional study of membrane proteins. Membrane proteins encapsulated by conventional headtotail detergents tend to undergo structural degradation, necessitating the development of structurally novel agents with improved efficacy. In recent years, facial amphiphiles have yielded encouraging results in terms of membrane protein stability. Herein, we report a new facial detergent (i.e., LFAC4) that confers greater stability to tested membrane proteins than the bola form analogue. Owing to the increased facial property and the adaptability of the detergent micelles in complex with different membrane proteins, LFAC4 yields increased stability compared to ndodecylβdmaltoside (DDM). Thus, this study not only describes a novel maltoside detergent with enhanced proteinstabilizing properties, but also shows that the customizable nature of a detergent plays an important role in the stabilization of membrane proteins. Owing to both synthetic convenience and enhanced stabilization efficacy for a range of membrane proteins, the new agent has major potential in membrane protein research.